Violent thoughts and fantasies in a high secure mentally disordered offender group: an exploratory study - Patel, Gita (2015)
There is a well-established association between thinking and doing and so it is no surprise that thinking about violence can be associated with risk of violent behaviour. Violent thoughts are recognised as a treatment target in many offender treatment programmes, yet given the multi-faceted nature of violent cognition and absence of integrating theory of violent offenders’ cognition it can sometimes be difficult to assess and treat the cognition that is associated with violent behaviour.